Classical Swine Fever in China-An Update Minireview - Zhou, Bin (Frontiers in Veterinary Science, 2019)
Classical swine fever (CSF) remains one of the most economically important viral diseases of domestic pigs and wild boar worldwide. The causative agent is CSF virus, it is highly contagious, with high morbidity and mortality rates; as such, it is an OIE-listed disease. Owing to a nationwide policy of vaccinations of pigs, CSF is well controlled in China, with large-scale outbreaks rarely seen. Sporadic outbreaks are however still reported every year. In order to cope with future crises and to eradicate CSF, China should strengthen and support biosecurity measures such as the timely reporting of suspected disease, technologies for reliable diagnoses, culling infected herds, and tracing possible contacts, as well as continued vaccination and support of research into drug and genetic therapies. This mini-review summarizes the epidemiology of and control strategies for CSF in China.